Childhood Obesity and Overweight Are Associated with Higher Risk of Depression and Anxiety: A Cross-Sectional Study in Children Aged 6–9 Years - Konstantinos Papadimitriou; Maria Mentzelou; Sousana K. Papadopoulou; Georgios Antasouras; Georgia-Eirini Deligiannidou; Olga Alexatou; Apostolia Ntovoli; Evmorfia Psara; Vasiliki G. Papadopoulou; Constantinos Giaginis (Life)
Background/Objectives: The global prevalence of childhood obesity and overweight is steadily increasing, representing a pressing public health concern due to its persistence during adolescence and adulthood and its association with elevated morbidity and mortality risks. This cross-sectional study was designed to examine the potential association between overweight/obesity and the presence of depressive and anxiety symptoms in children aged 6 to 9 years. Methods: A total of 4098 children from various urban and rural regions in Greece were enrolled. Data was collected through maternal questionnaires capturing sociodemographic characteristics, perinatal outcomes, anthropometric measurements, breastfeeding practices, and physical activity levels. Children fulfilled the Children’s Depression Inventory (CDI) and the State-Trait Anxiety Inventory for Children—State form (STAIC-S) to evaluate symptoms of depression and anxiety, respectively. Results: Childhood overweight/obesity was independently and significantly associated with a more than two-fold increased likelihood of presenting depressive and anxiety symptoms. Childhood overweight/obesity was also significantly associated with maternal obesity, gestational weight gain, childbirth weight, mode of delivery, exclusive breastfeeding, and children’s physical activity. Conclusions: Overweight and obesity in children aged 6–9 years are significantly associated with an elevated risk of psychological distress, including depression and anxiety. These findings underscore the need for targeted public health policies and nutritional interventions aimed at promoting healthy lifestyle practices from early childhood. Educational efforts should also support new mothers in adopting and sustaining health-promoting behaviors to mitigate the long-term consequences of childhood obesity.